Maeve's times [large type]: in her own words - Binchy, Maeve, 1940-2012 (Thorndike Press, 2014)
Collects the best of the author's essays from five decades of the "Irish Times" to reflect a changing culture as well as her observations on such topics as the royal wedding, waitressing, and boring airline companions.